Key to the genus Megachile, Chalicodoma group (Hymenoptera: Megachilidae) in Cuba - Genaro, Julio A (1996)
The megachilid bees of the Chalicodoma group includes four species in Cuba: Megachilé armaticeps, M. lanata, M. rufipennis and M. torrida. The last three species are adyentiyes while M. atriceps is endemic. An illustrated key to species is included.